Indications of Root Canal Treatment for Patients Visiting Tertiary Care Hospital: A Hospital Based Prospective Study - Manisha Nepal; Snigdha Shubham; Rupam Tripathi; Jwolan Khadka; Kriti Shrestha (Journal of Universal College of Medical Sciences, 2023)
INTRODUCTIONRoot Canal Treatment (RCT) when an irreversibly damaged or necrotic pulp with or without clinical and/or radiological ﬁndings of apical periodontitis occur. Apart from these there are various other reasons in which RCT is performed. There is paucity of literature revealing diseases requiring RCT and what are the presenting symptoms for patients requiring it. Hence, this study is conducted to overview the factors for it.MATERIAL AND METHODSAmong 594 patients, 510 were included in the study. The survey form included patient speciﬁc characteristics such as: age, gender, tooth number and pain; tooth speciﬁc characteristic included swelling, previous root canal treatment, complain tooth characteristic, diagnosis and tooth wear. These data were matched with the respective radiograph and history form sheet. Two observers participated in collection of data in the study. Inter-observer agreement was tested with Cronbach’s alpha which was 0.79. The data were collected in a spreadsheet and simple descriptive statistical analysis was performed using SPSS software version 22 to get the results in percentages and frequencies.RESULTS54.1% of female patients had undergone RCT and 75.7% of patients presented with pain. The most common treated tooth was ﬁrst molar. The most common pulpal diagnosis was symptomatic irreversible pulpitis (36.08%, n=184) followed by pulp necrosis (30.20%, n=154) and previously treated (17.25%, n=88). The most common periapical diagnosis was symptomatic apical periodontitis (62.94%, n=321).CONCLUSIONSubjective symptoms were the most common factor for seeking treatment. Hence, a greater number of awareness campaign are required to acknowledge asymptomatic cases too.